Causal effect of pandemic COVID-19, gold and oil prices on United States economic policy uncertainty: Evidence from ARDL method - Siddique, Asima; khan, Muhammad Asif; Khalid, Ali Awais (Journal of Business & Tourism, 2022)
The United States is the most significant economic power in the world. Therefore changes in economic indicators or economic policy of the United States will affect the whole world economy like the global financial crisis 2007-08. The first innovative study examines the effect of United States Coronavirus (COVID-19), oil, and gold prices on United States economic policy uncertainty. Autoregressive Distributed Lag Model(ARDL) is employed to get the long and short-run co-integration results. The outcome shows that (USCOVID_19 and OIL) significantly co-integrated in both the short and long run with United State Economic Policy of Uncertainty(USEPU) at a significant level. USCOVID-19 is positively short and long-run co-integrated, while oil is negatively short and long-run co-integrated with the economic uncertainty level of the USEPU. Only one variable of gold has no short and long-run co-integrated with USEPU.